Digital Media Based On Quantum Learning to Increase Learning Motivation and Student Learning Activities In Mathematics - Dewi, Sopian; Mandailina, Vera; Mahsup, Mahsup; Syaharuddin, Syaharuddin; Iddrisu, Mohammed Muniru; AHMODU, Abdul-Lateef Olamide (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
Learning with the quantum learning model is one of the learning methods in its implementatied Learning with the quantum learning model is one of the learning methods in its implementation enjoy being more active in discussing and working together in class. This study aims to determine the effect of the application of the quantum learning model on increasing student motivation and learning activities. This research is experimental quantitative research consisting of two classes, namely the control class and the experimental class. Data collection instruments used questionnaires.Data analysis used in this study is a descriptive test, normality test, and paired sample test. The results of the normality test (Shapiro-Wilk) for learning motivation of the control class and experimental class amounted to 0.147 greater than 0.05 and for learning activities of the control class and experimental class amounted to 0.362 greater than 0.05. T-test for learning motivation showed that the improvement of the experimental class was higher than the control class (t = -0.785 p = 0.220 > 0.05) and the SE value of Cohen's d (0.317). The T-test for learning activities showed that the increase in learning motivation of the experimental class was higher than that of the control class (t = -2.506 p = 0.009 < 0.05) and the SE Cohen's d value (0.194).That's whybased on the results show that the quantum learning model can increase student learning motivation.